Clitoral Epidermoid Cyst Presenting as Pseudoclitoromegaly of Pregnancy - Jing W. Hughes; Marsha K. Guess; Adam Hittelman; Sallis Yip; John Astle; Lubna Pal; Silvio E. Inzucchi; Antonette T. Dulay (Thieme Medical Publishers, Inc., 2013)
Abstract Objective Acquired clitoromegaly is rare and may result from hormonal and nonhormonal causes, and evaluation of the pregnant patient with clitoromegaly invokes a specific set of differential diagnoses. Methods Case report. Results We describe the case of a young woman with pregnancy-associated clitoral enlargement whose hormonal evaluation proved negative. Further investigation concluded that an epidermoid cyst was the culprit of her pseudoclitoromegaly. The patient underwent successful surgical resection and has had no recurrence at her subsequent pregnancy. Conclusion We review the differential diagnosis of clitoromegaly, including hormonal and nonhormonal causes, with focus on the evaluation of pregnancy-associated clitoromegaly.